Presencia de la familia Pompilidae (Insecta, Hymenoptera) en el Mioceno Superior de la Cuenca de La Cerdaña - Arillo, Antonio (Coloquios de Paleontología, 2001)
In this paper the family Pompilidae (Insecta, Hymenoptera) is recorded for the first time as fossil from the Iberian Peninsula. Two specimen appeared in Bellver de Cerdanya (Lleida, Spain, Upper Miocene) both belonging to the subgenus Dipogon (Deuteragenia) SUSTERA, 1913. These fossils are compared with previously known fossil records of this family, mainly with two very close species: Priocnemis aertsi STAZT, 1936 and Priocnemis wettweri STATZ, 1938, from the Oligocene of Rött (Rheinland, Germany).
Keywords: Insecta; Hymenoptera; Pompilidae; Miocene; Spain